Saudi Arabia’s contribution to systematic reviews in dentistry: A bibliometric analysis - Swapna Munaga; Aram Alshehri; Ikram Ul-Haq; Sara Kalagi; Rajkiran Chitumalla; Kiran Iyer (Saudi Dental Journal)
Background/objectives: Bibliometric is a quantitative assessment method to identify prevailing trends and patterns of publications in a particular field of study. Systematic Reviews (SRs) give an in-depth study of the literature and the most comprehensive overview of the desired research subject. This study aimed to review the bibliometric properties of SRs published by the dentists of Saudi Arabia. Materials and methods: Relevant dataset of SRs on dentistry with at least one author affiliated with Saudi Arabia from PubMed database was obtained. Each document of the retrieved data was screened based on the inclusion and exclusion criteria. The citation metric was collected from Google Scholar. Results: A total of 625 SRs published from the year 2007 to 2023 were included. The average number of citations for each of these SRs is 25.54. Though a low productivity was observed until 2017, the number of SRs published has increased in the previous three years. SRs in Prosthodontics were the most prevalent. The SRs with the first author from Saudi Arabia and internationally collaborated gained a higher citation impact. Most of the SRs were published in the Saudi Dental Journal. Authors from King Saud University contributed to more than a quarter of the SRs. The two nations that collaborated the most SRs were found to be United States and India. Conclusion: Over the last three years, there has been significant progress in the publishing of SRs from Saudi Arabia. The bibliometric parameters identified in this study support researchers in understanding the current status of SRs publication. There is a need to increase awareness about the importance of high-evidence research in dentistry and enhance the training opportunities as well as research incentives for this kind of scientific production.